Concealed complete response in melanoma patients under therapy with immune checkpoint inhibitors: two case reports - Schliep, Stefan; Agaimy, Abbas; Kiesewetter, Franklin; Schuler, Gerold; Heinzerling, Lucie; Cavallaro, Alexander Josef (Journal for ImmunoTherapy of Cancer, 2018)
BACKGROUND: The assessment of tumor size by RECIST using CT scans and MRIs is considered to be standard of care for staging cancer patients. Despite radiologic evidence of widespread disease, we document for the first time that patients were completely free of viable tumor. CASE PRESENTATION: Two patients with metastatic melanoma were treated with immune checkpoint inhibitors (ipilimumab/ nivolumab) and progressive metastases were detected on CT-scans performed shortly before histologic examinations. In both patients histologic assessment revealed a complete response with necrotic and scarred lesions free of tumor. One of the patients had started immunotherapy 20 months before with an initial partial response. CONCLUSIONS: This phenomenon of a concealed complete response can lead to overtreatment or unnecessary change in treatment. Thus, it is essential to raise awareness for it. Correct identification of responders to immune checkpoint inhibitor therapy is crucial to spare patients immune-mediated side effects and unnecessary as well as expensive treatment. Regression of metastases without decline in size, in these cases manifesting as complete responses, are probably more common than expected and identified to date. Until such responses can be readily identified by new imaging techniques, we recommend liberal biopsies for histologic assessment of progressive metastases in patients during and/or after immune checkpoint inhibitor therapy.
EVALuna2:34405

Dermal absorption and skin damage following hydrofluoric acid exposure in an ex vivo human skin model - Dennerlein, Kathrin; Kiesewetter, Franklin; Kilo, Sonja; Jäger, Thomas; Göen, Thomas; Korinth, Gintautas; Drexler, Hans (Toxicology Letters, 2016)
The wide industrial use of hydrofluoric acid (HF) poses a high risk for accidental dermal exposure. Despite local and systemic hazards associated with HF, information on percutaneous penetration and tissue damage is rare. In the present ex vivo study, the dermal absorption of HF (detected in terms of fluoride ions) was quantified and the skin damaging potential as a function of concentration and exposure duration was assessed. Percutaneous penetration of HF (c=5, 30, and 50%) at 3 exposure durations (3, 5, and 10min) was investigated in a static diffusion cell model using freshly excised human skin. Alterations of skin were histologically evaluated. HF rapidly penetrated through skin under formation of a considerable intradermal reservoir ( 13-67% of total absorbed fluoride). Histologically, epidermal alterations were detected already after exposure to 5% HF for 3min. The degree of skin damage increased with rising concentration and exposure duration leading to coagulation necrosis. For HF concentrations of >=30%, skin damage progressed into deeper skin layers. Topically applied HF concentration was the principal parameter determining HF induced skin effects. The intradermal HF retention capacity associated with progression and prolongation of HF induced skin effects must be considered in the review of skin decontamination procedures.
EVALuna2:9745

Disseminated Pustules in a 3 Year Old Boy - Grosch, Ella; Koeceroglu, M.; Schliep, S.; Kiesewetter, Franklin; Sticherling, Michael; Voskens, C. J. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Drug-induced dilemma: angiokeratomas and decreased renal function - Schliep, Stefan; Kiesewetter, Franklin; Simon, Miklos; Grupp, Clemens; Heinzerling, Lucie (American Journal of Medicine, 2014)
EVALuna2:19482

Fumaric Acid Esters and TNF alpha Inhibitors - Do they affect the Fertility of male Patients with Psoriasis? - Heppt, Franz; Colsmann, A.; Maronna, A.; Uslu, Ugur; Heppt, M.; Kiesewetter, Franklin; Sticherling, Michael (2017)
EVALuna2:34352

Genotype-phenotype correlation in boys with X-linked hypohidrotic ectodermal dysplasia - Burger, Kristin; Schneider, Anne-Theres; Wohlfart, Sigrun; Kiesewetter, Franklin; Huttner, Kenneth; Johnson, Ramsey; Schneider, Holm (American Journal of Medical Genetics Part A, 2014)
X-linked hypohidrotic ectodermal dysplasia (XLHED), the most frequent form of ectodermal dysplasia, is a genetic disorder of ectoderm development characterized by malformation of multiple ectodermal structures such as skin, hair, sweat and sebaceous glands, and teeth. The disease is caused by a broad spectrum of mutations in the gene EDA. Although XLHED symptoms show inter-familial and intra-familial variability, genotype-phenotype correlation has been demonstrated with respect to sweat gland function. In this study, we investigated to which extent the EDA genotype correlates with the severity of XLHED-related skin and hair signs. Nineteen male children with XLHED (age range 3-14 years) and seven controls (aged 6-14 years) were examined by confocal microscopy of the skin, quantification of pilocarpine-induced sweating, semi-quantitative evaluation of full facial photographs with respect to XLHED-related skin issues, and phototrichogram analysis. All eight boys with known hypomorphic EDA mutations were able to produce at least some sweat and showed less severe cutaneous signs of XLHED than the anhidrotic XLHED patients (e.g., perioral and periorbital eczema or hyperpigmentation, regional hyperkeratosis, characteristic wrinkles under the eyes). As expected, individuals with XLHED had significantly less and thinner hair than healthy controls. However, there were also significant differences in hair number, diameter, and other hair characteristics between the group with hypomorphic EDA mutations and the anhidrotic patients. In summary, this study indicated a remarkable genotype-phenotype correlation of skin and hair findings in prepubescent males with XLHED.
EVALuna2:18885

Human AZFb deletions cause distinct testicular pathologies depending on their extensions in Yq11 and the Y haplogroup: new cases and review of literature - Vogt, P. H.; Bender, U.; Deibel, B.; Kiesewetter, Franklin; Zimmer, J.; Strowitzki, T. (Cell & Bioscience, 2021)
Genomic AZFb deletions in Yq11 coined “classical” (i.e. length of Y DNA deletion: 6.23 Mb) are associated with meiotic arrest (MA) of patient spermatogenesis, i.e., absence of any postmeiotic germ cells. These AZFb deletions are caused by non-allelic homologous recombination (NAHR) events between identical sequence blocks located in the proximal arm of the P5 palindrome and within P1.2, a 92 kb long sequence block located in the P1 palindrome structure of AZFc in Yq11. This large genomic Y region includes deletion of 6 protein encoding Y genes, EIFA1Y, HSFY, PRY, RBMY1, RPS4Y, SMCY. Additionally, one copy of CDY2 and XKRY located in the proximal P5 palindrome and one copy of BPY1, two copies of DAZ located in the P2 palindrome, and one copy of CDY1 located proximal to P1.2 are included within this AZFb microdeletion. It overlaps thus distally along 2.3 Mb with the proximal part of the genomic AZFc deletion. However, AZFb deletions have been also reported with distinct break sites in the proximal and/or distal AZFb breakpoint intervals on the Y chromosome of infertile men. These so called “non-classical” AZFb deletions are associated with variable testicular pathologies, including meiotic arrest, cryptozoospermia, severe oligozoospermia, or oligoasthenoteratozoospermia (OAT syndrome), respectively. This raised the question whether there are any specific length(s) of the AZFb deletion interval along Yq11 required to cause meiotic arrest of the patient’s spermatogenesis, respectively, whether there is any single AZFb Y gene deletion also able to cause this “classical” AZFb testicular pathology? Review of the literature and more cases with “classical” and “non-classical” AZFb deletions analysed in our lab since the last 20 years suggests that the composition of the genomic Y sequence in AZFb is variable in men with distinct Y haplogroups especially in the distal AZFb region overlapping with the proximal AZFc deletion interval and that its extension can be “polymorphic” in the P3 palindrome. That means this AZFb subinterval can be rearranged or deleted also on the Y chromosome of fertile men. Any AZFb deletion observed in infertile men with azoospermia should therefore be confirmed as “de novo” mutation event, i.e., not present on the Y chromosome of the patient’s father or fertile brother before it is considered as causative agent for man’s infertility. Moreover, its molecular length in Yq11 should be comparable to that of the “classical” AZFb deletion, before meiotic arrest is prognosed as the patient’s testicular pathology.
CRIS-Team Scopus Importer:2021-05-14
Keywords: AZFb Y genes; AZFb “de novo” and “polymorphic” deletions; AZFb-c amplicons; Meiotic arrest; OAT syndrome; Y-haplogroups; “Classical” and “non-classical” AZFb deletions

Influence of TNF-alpha inhibitors and fumaric acid esters on male fertility in psoriasis patients - Heppt, Franz; Colsman, A.; Maronna, A.; Uslu, Ugur; Heppt, M. V.; Kiesewetter, Franklin; Sticherling, Michael (Journal of the European Academy of Dermatology and Venereology, 2017)
OBJECTIVE: Is there any influence of a therapy with TNF-alpha inhibitors or fumaric acid esters and of disease activity status on male fertility and sperm quality in patients with psoriasis? METHODS: In this monocentric, open-label, prospective study, semen samples were collected from patients receiving either TNF-alpha inhibitors or fumaric acid esters for moderate-to-severe plaque psoriasis. Semen was analysed at baseline before onset of the systemic therapy and monitored every 3 months under therapy. Sperm parameters were assessed according to the current WHO definitions. RESULTS: In total, 101 semen specimens from 27 patients were obtained. Mean Psoriasis Area and Severity Index (PASI) score at baseline was 11.05. Only 14.8% of patients showed a normozoospermia without any other abnormal seminal values. 85.2% of patients had at least one sperm/seminal abnormality, including two patients showing an azoospermia. Interestingly, 48.1% showed sperm parameters indicative of genital tract inflammation. Therapy with TNF-alpha inhibitors or fumaric acid esters did not have any negative effects on relevant sperm parameters such as mean total sperm number, sperm concentration, total and progressive motility. No major gonadal dysfunction was observed in any patient. CONCLUSION: At baseline, many patients with psoriasis showed abnormal semen/sperm parameters and remarkably elevated leukocytes and values of seminal polymorphonuclear elastase, indicating a genital tract inflammation. Thus, genital tract inflammation may represent an important comorbidity of psoriasis, little attention paid to so far. Regarding treatment with TNF-alpha inhibitors or fumaric acid esters, no major negative (side-) effects on sperm quality were observed.
EVALuna2:34337

Kutane's plasma-cell-rich Pseudolymphoma in histologically complete Response under combined Immunotherapy with Talimogene laherparepvec (TVEC) and Pembrolizumab - Erdmann, M.; Sponagl, F.; Kiesewetter, Franklin; Schliep, S. (2018)
EVALuna2:34777

Look-alikes with opposite consequences: Cutaneous Botryomycosis presenting as cutaneous metastases in a patient with a history of metastatic lung cancer - Bosch-Voskens, C.; Woerl, P.; Kiesewetter, Franklin; Schliep, S. (2017)
EVALuna2:34368

Pancreatic panniculitis in a patient with pancreatic-type acinar cell carcinoma of the liver–case report and review of literature - Zundler, Sebastian; Erber, Ramona; Agaimy, Abbas; Hartmann, Arndt; Kiesewetter, Franklin; Strobel, Deike; Neurath, Markus; Wildner, Dane (BMC Cancer, 2016)
Pancreatic panniculitis is a rare condition, which has only been described in relation with pancreatic diseases up to now. It is characterized by necrotizing subcutaneous inflammation and is thought to be triggered by adipocyte necrosis due to systemic release of pancreatic enzymes with consecutive infiltration of neutrophils. We present the first case of a patient with pancreatic panniculitis caused by pancreatic-type primary acinar cell carcinoma (ACC) of the liver and without underlying pancreatic disease.A 73-year old Caucasian female patient was referred to our department with painful cutaneous nodules persisting for eight weeks and with marked lipasemia ( 15000 U/l; normal range <60 U/l). Four weeks prior, several liver lesions had been detected. Empiric treatment with steroids did not show any effect. A biopsy of the skin nodules revealed "pancreatic" panniculitis, while abdominal imaging with ultrasound, computed tomography and magnetic resonance imaging detected no abnormal pancreatic findings. Ultrasound-guided biopsy of the liver lesions showed infiltrates of an ACC. The patient died soon thereafter. Autopsy failed to reveal any other primary for the ACC, so that a pancreatic-type ACC of the liver was diagnosed by exclusion. One hundred thirty cases of pancreatic panniculitis published within the last 20 years are reviewed. ACC of the pancreas is the most common underlying neoplastic condition. Patients with associated neoplasm are significantly older, take longer to be diagnosed and have higher lipase levels than patients with underlying pancreatitis. Extrapancreatic pancreatic-type ACC is very rare, but shows the same biological features as ACC of the pancreas. It is believed to develop from metaplastic or ectopic pancreatic tissue. Up to now, no pancreatic panniculitis in extrapancreatic ACC has been described.Pancreatic panniculitis should always be included in the differential diagnosis of lipolytic panniculitic lesions. It can be regarded as a facultative paraneoplastic phenomenon. When suspected, a thorough work-up for identification of the underlying disease is mandatory and extrapancreatic lesions (e.g. liver) should also be considered. While administration of octreotide or steroids can sometimes alleviate symptoms, immediate treatment of the associated condition is the only effective management option.
EVALuna2:2057

Predictive value of PD-L1 based on mRNA level in the treatment of stage IV melanoma with ipilimumab - Brueggemann, C.; Kirchberger, M. C.; Goldinger, S. M.; Weide, B.; Konrad, A.; Erdmann, M.; Schadendorf, D.; Croner, R. S.; Krahenbuhl, L.; Kaehler, K. C.; Hafner, C.; Leisgang, W.; et al. (Journal of Cancer Research and Clinical Oncology, 2017)
PD-L1 is established as a predictive marker for therapy of non-small cell lung cancer with pembrolizumab. Furthermore, PD-L1 positive melanoma has shown more favorable outcomes when treated with anti-PD1 antibodies and dacarbazine compared to PD-L1 negative melanoma. However, the role of PD-L1 expression with regard to response to checkpoint inhibition with anti-CTLA-4 is not clear, yet. In addition, the lack of standardization in the immunohistochemical assessment of PD-L1 makes the comparison of results difficult. In this study, we investigated the PD-L1 gene expression with a new fully automated technique via RT-PCR and correlated the findings with the response to the anti-CTLA-4 antibody ipilimumab.Within a retrospective multi-center trial, PD-L1 gene expression was evaluated in 78 melanoma patients in a total of 111 pre-treatment tumor samples from 6 skin cancer centers and analyzed with regard to response to ipilimumab. For meaningful statistical analysis, the cohort was enriched for responders with 30 responders and 48 non-responders. Gene expression was assessed by quantitative RT-PCR after extracting mRNA from formalin-fixed paraffin embedded tumor tissue and correlated with results from immunohistochemical (IHC) stainings.The evaluation of PD-L1 expression based on mRNA level is feasible. Correlation between PD-L1 expression as assessed by IHC and RT-PCR showed varying levels of concordance depending on the antibody employed. RT-PCR should be further investigated to measure PD-L1 expression, since it is a semi-quantitative method with observer-independent evaluation. With this approach, there was no statistical significant difference in the PD-L1 expression between responders and non-responders to the therapy with ipilimumab. The evaluation of PD-L1 expression based on mRNA level is feasible. Correlation between PD-L1 expression as assessed by IHC and RT-PCR showed varying levels of concordance depending on the antibody employed. RT-PCR should be further investigated to measure PD-L1 expression, since it is a semi-quantitative method with observer-independent evaluation. With this approach, there was no statistical significant difference in the PD-L1 expression between responders and non-responders to the therapy with ipilimumab.
EVALuna2:15289

Soluble CD83 improves and accelerates wound healing by the induction of pro-resolving macrophages - Royzman, Dmytro; Peckert-Maier, Katrin; Stich, Lena; König, Christina; Wild, Andreas; Tauchi, Miyuki; Ostalecki, Christian; Kiesewetter, Franklin; Seyferth, Stefan; Lee, Geoffrey; Eming, Sabine A.; Fuchs, Maximilian; et al. (Frontiers in Immunology, 2022)
To facilitate the recovery process of chronic and hard-to-heal wounds novel pro-resolving treatment options are urgently needed. We investigated the pro-regenerative properties of soluble CD83 (sCD83) on cutaneous wound healing, where sCD83 accelerated wound healing not only after systemic but also after topical application, which is of high therapeutic interest. Cytokine profile analyses revealed an initial upregulation of inflammatory mediators such as TNFα and IL-1β, followed by a switch towards pro-resolving factors, including YM-1 and IL-10, both expressed by tissue repair macrophages. These cells are known to mediate resolution of inflammation and stimulate wound healing processes by secretion of growth factors such as epidermal growth factor (EGF) and vascular endothelial growth factor (VEGF), which promote vascularization as well as fibroblast and keratinocyte differentiation. In conclusion, we have found strong wound healing capacities of sCD83 beyond the previously described role in transplantation and autoimmunity. This makes sCD83 a promising candidate for the treatment of chronic- and hard-to-heal wounds.
CRIS-Team Scopus Importer:2022-10-28
Keywords: CD83; macrophages; stem cells; therapy; tissue regeneration; wound healing

Soluble CD83 promotes cutaneous wound healing in an IDO-and beta-catenindependent manner - Royzman, Dmytro; Peckert-Maier, K.; Stich, L.; Wild, Andreas; Ostalecki, C.; Kiesewetter, Franklin; Seyferth, Stefan; Lee, Geoffrey; Eming, S. A.; Berking, Carola; Zinser, Elisabeth; Steinkasserer, Alexander (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

TRICHODYSPLASIA SPINULOSA WITH DISFIGURING FACIAL FEATURES AFTER KIDNEY TRANSPLANTATION IMPROVED BY mTOR-INHIBITION - Dieterle, A.; Korn, Klaus; Büttner, Maike; Schiffer, Mario; Kiesewetter, Franklin; Wiesener, M. S. (TRANSPLANT INTERNATIONAL, 2019)
CRIS-Team WoS Importer:2019-10-29